DESIGN FOR ADDITIVE MANUFACTURING AND CUSTOMIZATION: A CONTEMPORARY REVIEW - Manal Abdul Hameed Abdul Majeed; Hamid Shakir Mahmoud; Hussam Abdulameer Mohammed Alsalman (Scholars Digest Publishing, 2024)
Additive design is one of the most important advanced manufacturing techniques, as it is one of the contemporary intellectual approaches in the field of production and operations management for its vital and essential role in providing a set of economic, social and environmental benefits to the organization using this technology. Hence, the current paper was presented to focus on the additive design, which is one of the pillars of additive manufacturing technology, which is one of the cognitive and intellectual entrances under formation and cognitive and applied framing, and measuring its role in contributing to the improvement of product recommendations and production according to the design provided by the customer. where the problem of the current paper was to measure the possibility of applying additive design technology in the Iraqi industrial organizations and its impact on the allocation of products. The researchers employed the case study method to measure and test the hypothetical research scheme. The Ibn Majid General Industrial Company in Basra was chosen to implement the current study and test the hypotheses. The results of the statistical analysis showed that additive design technology contributes to improving product design and customization.
Keywords: Additive Design, Customization, Sustainability, 3D printer, additive manufacturing, advanced manufacturing techniques, product design.